Altruism, Education Subsidy and Growth - Mauricio Armellini; Parantap Basu (Economics and Econometrics Research Institute (EERI), 2010)
An optimal education subsidy formula is derived using an overlapping generations model with parental altruism. The model predicts that public education subsidy is greater in economies with lesser parental altruism because a benevolent government has to compensate for the shortfall in private education spending of less altruistic parents with a finite life. On the other hand, growth is higher in economies with greater parental altruism. Cross-country regressions using the World Values Survey for altruism lend support to our model predictions. The model provides insights about the reasons for higher education subsidy in richer countries.
Keywords: D9; 330; Altrusim; Education Subsidy; Human Capital; Growth